Mixing Properties of Cu-Mg Liquid Alloy Using Exponential Model - Yadav, Shahsit Kumar; GC, Dinesh; Gohivar, Ramesh Kumar; Mehta, Upendra; Adhikari, Devendra; Koirala, Ram Prasad (Journal of Institute of Science and Technology, 2023)
The Redlich-Kister (R-K) polynomial has been generally used to model the mixing properties of binary and higher order alloys. The interaction energy parameters of the R-K polynomial are assumed to be either linear or exponentially temperature-dependent. When these parameters are assumed to be linear temperature-dependent, the computed thermodynamic functions sometimes show unusual trends. But when they are assumed to be exponential temperature-dependent, such trends do not appear in the theoretical calculations. Therefore, the mixing properties of Cu-Mg liquid alloy have been studied using the exponential temperature-dependent parameters of the above-mentioned model. These parameters for excess Gibb’s free energy of mixing have been optimised using the experimental values of enthalpy of mixing and excess entropy of mixing. The study of thermodynamic properties involves the measurement of excess Gibb’s free energy of mixing, enthalpy of mixing and activities of monomers at different temperatures. Likewise, the assessment of surface property includes surface tension and surface concentration. Similarly, the structural properties have been studied by computing concentration fluctuation in long wave-length limit and short-range order parameter at different temperatures. The investigation revealed that the exponential model can explain mixing behavior of Cu-Mg liquid alloy and the system is found to have strong compound forming tendency at its melting temperature. This mixing tendency has been observed to decrease with the increase in temperature above its melting temperature.